White Paper: Movement System Diagnoses in Neurologic Physical Therapy. Issue 2 (April 2018) - Hedman, Lois D.; Quinn, Lori; Gill-Body, Kathleen; Brown, David A.; Quiben, Myla; Riley, Nora; Scheets, Patricia L.
Abstract : Background and Purpose: The APTA recently established a vision for physical therapists to transform society by optimizing movement to promote health and wellness, mitigate impairments, and prevent disability. An important element of this vision entails the integration of the movement system into the profession, and necessitates the development of movement system diagnoses by physical therapists. At this point in time, the profession as a whole has not agreed upon diagnostic classifications or guidelines to assist in developing movement system diagnoses that will consistently capture an individual's movement problems. We propose that, going forward, diagnostic classifications of movement system problems need to be developed, tested, and validated. The Academy of Neurologic Physical Therapy's Movement System Task Force was convened to address these issues with respect to management of movement system problems in patients with neurologic conditions. The purpose of this article is to report on the work and recommendations of the Task Force. Summary of Key Findings: The Task Force identified 4 essential elements necessary to develop and implement movement system diagnoses for patients with primarily neurologic involvement from existing movement system classifications. The Task Force considered the potential impact of using movement system diagnoses on clinical practice, education and, research. Recommendations were developed and provided recommendations for potential next steps to broaden this discussion and foster the development of movement system diagnostic classifications. Recommendations for Clinical Practice: The Task Force proposes that diagnostic classifications of movement system problems need to be developed, tested, and validated with the long-range goal to reach consensus on and adoption of a movement system diagnostic framework for clients with neurologic injury or disease states. Video Abstract available for more insights from the authors (see Video, Supplemental Digital Content 1, available at:http://links.lww.com/JNPT/A198 ). Abstract : Supplemental Digital Content is Available in the Text.